2016
DOI: 10.1186/s13098-016-0176-y
|View full text |Cite
|
Sign up to set email alerts
|

Skin disorders in diabetes mellitus: an epidemiology and physiopathology review

Abstract: Skin disorders, usually neglected and frequently underdiagnosed among diabetic patients, are common complications and encounter a broad spectrum of disorders in both type 1 and type 2 diabetes mellitus (DM)—e.g. cutaneous infection, dry skin, pruritus. Skin disorders are highly associated with increased risk of important outcomes, such as skin lesions, ulcerations and diabetic foot, which can lead to major complications and revolve around multifactorial factors besides hyperglycemia and advanced glycation end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(146 citation statements)
references
References 49 publications
4
107
0
21
Order By: Relevance
“…The formation of advanced glycation end products reduces the elasticity and solubility of collagen, enhances its stiffness [58,178]. The results presented in Ref.…”
Section: Skinmentioning
confidence: 80%
See 4 more Smart Citations
“…The formation of advanced glycation end products reduces the elasticity and solubility of collagen, enhances its stiffness [58,178]. The results presented in Ref.…”
Section: Skinmentioning
confidence: 80%
“…For example, in Refs. [58,156] it was concluded that the glycation of collagen under diabetes mellitus facilitates the development of fibrosis. In turn, the structural changes of tissue proteins lead to the change of their optical properties.…”
Section: Different Tissuesmentioning
confidence: 99%
See 3 more Smart Citations